Cardiac anesthesia in BSMMU from December 2003 to April 2008 - an audit - Rahman, Z; Ahsan, N; Khan, F; Ahsan, SF; Rahman, AKMS (University Heart Journal, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> BSMMU cardiac anesthesia unit started functioning in 2003 when Cardiovascular Surgery department was established. Initial shortcomings were overcome and the cardiac anesthesia unit started working in full swing as a specialized branch of the department of Anesthesia, Analgesia & Intensive Care Medicine, BSMMU. The Cardiac Surgery department and cardiac anesthesia unit has been working in joint collaboration for the management of cardiac surgical patients. Cardiac anesthesia unit is carrying the responsibilities of perioperative care of the cardiac surgical patients, such as preoperative assessment, peroperative anesthetic management, post-operative care in cardiac intensive care unit. Besides, care for the patients during cathlab procedures and life-saving or invasive procedures for patients in coronary care unit are also within the duties of doctors working in cardiac anesthesia unit. Patients operated for vascular diseases are also attended in the same OT and ICU complex. This audit is done to report developments of performance and annual assessment of the number of cases, their anesthetic supports & their outcomes in cardiac anesthesia practice in BSMMU. Â  University Heart Journal Vol.4(1) January 2008